Quantification, administrative capacity and democracy: database of performance indicators used for the steering of hospitals, universities and prisons in England, 1985-2015 - Mennicken, Andrea 19XX- (UK Data Service, 2021)
This database seeks to capture the rise and extent of quantification as a tool of government by tracing the development of performance indicators used for regulatory purposes between 1985 and 2015 across different public service sectors (health/hospitals; higher education/universities; criminal justice/prisons) in the UK (with a specific focus on England). The cross-sectoral comparison intends to capture the diffusion of indicators across domains, and to compare temporal dynamics in the adoption of similar or different new public management instruments: Do indicators develop in a similar pace across sectors? What are their focus, audience and goals? And how did these change over time? Numbers increasingly govern public services. Both policymaking activities and administrative control are increasingly structured around calculations such as cost-benefit analyses, estimates of social and financial returns, measurements of performance and risk, benchmarking, quantified impact assessments, ratings and rankings, all of which provide information in the form of a numerical representation. Through quantification, public services have experienced a fundamental transformation from government by rules to governance by numbers, with fundamental implications not just for our understanding of the nature of public service itself, but also for wider debates about the nature of citizenship and democracy. This project scrutinizes the relationships between quantification, administrative capacity and democracy across three policy sectors (health/hospitals, higher education/universities, criminal justice/prisons) and four countries (France, Germany, Netherlands, UK). It offers a cross-national and cross-sectoral study of how managerialist ideas and instruments of quantification have been adopted and how they mattered. More specifically, it examines (i) how quantification has travelled across sectors and states; (ii) relations between quantification and administrative capacity; and (iii) how quantification has redefined relations between public service and liberal democratic understandings of public welfare, notions of citizenship, equity, accountability and legitimacy.